Students’ learning motivation in English for specific purpose in Chinese universities - Guosheng, Xu; Xiaoyu, Zhang; Baihui, Qian (Institute of Advanced Engineering and Science, 2024)
A large number of studies at home and abroad have demonstrated the importance of university students’ English learning motivation, but few studies have focused on a certain field, or students’ major particularly under the context of Chinese private university. This research explores students’ motivation to learn English for specific purposes (ESP), and 123 student participants majoring in mechanical and electronic engineering in Shandong Huayu University of Technology participated in the research. Data are presented qualitatively and quantitatively. Students filled in a quantitative questionnaire about learning motivation, then SPSS27 was used to analyze relevant data. In addition, focus group interview, as a qualitative means, was used in the research, and 12 student participants who were going to attend ESP class showed their opinions in the group interview. The results showed that students’ learning motivation comes more from teachers’ personal charm, harmonious teacher-student relationship and comfortable and warm learning environment, while setting difficult tasks for them is not their main motivation. The research results provide a useful reference for teachers to adopt teaching practices that motivate students to learn in ESP class.